Efeito do uso local e sistêmico da calcitonina em defeitos periodontais de ratos Wistar: estudo histomorfométrico e imunoistoquímico - Lustosa, Leodgar Luiz (2011)
The oral biofilm, in healthy subjects, have in their composition a predominance of Gram-positive cocci and some Gram-negative aerobic or facultative aerobes. This composition is altered when an accumulation of plaque occurs, making it thicker, decreasing the level of available oxygen, predisposing to a higher survival of anaerobic microorganisms. The microbial communities of biofilms, associated with an inflammatory response of host have high capacity of localized tissue destruction around the teeth, leading to periodontal disease with bone loss of insertion. The alveolar bone, which participates in the formation of periodontal support, remodels itself throughout life and is influenced by various types of hormones such as calcitonin. Calcitonin is a hormone produced by the thyroid gland, with an important role in inhibiting bone resorption and osteoclastic activity. Few studies have evaluated the treatment of periodontal lesions treated with procedures for scaling and root planning (SRP), combined with the local administration of calcitonin. Our aim was to evaluate the use of systemic and local administration of calcitonin associated with SRP, for bone regeneration of periodontal defects. Were used forty male Wistar rats, in which periodontal disease was induced by ligature. After induction of periodontal disease, the rats were divided into four groups, the following treatments: a) control (ligation only), b) SRP, c) systemic administration of calcitonin associated with SRP, d) local administration of calcitonin associated with SRP. Analyses were performed in two stages: seven to fifteen days after the treatments. The changes caused by the administration of calcitonin were evaluated by histopathological examinations. The application of calcitonin caused significant results regarding the parameters: extension of the sulcus and junctional epithelium, and distance between the cement-enamel junction and bone crest mesial and between cement and boné tissue in the furcation area. The best results were those observed in the systemic form of application of the drug, within fifteen days. Based on the methodology used, we can assert that calcitonin associated basic periodontal treatment promoted improvement in the histopathological aspects of soft tissue and periodontal resorption inhibiting bone